An unusual case of left hepatectomy for Focal Nodular Hyperplasia (FNH) linked to the use of Anabolic Androgenic Steroids (AASs). (2017) - Romano, Angela; Grassia, Michele; Esposito, Giuseppe; Petrillo, Marianna; Pezzella, Modestino; Romano, Francesco Maria; Esposito, Francesco; Torelli, Francesco; Di Martino, Natale
Highlights: This is an unusual case of left hepatectomy for FNH. Focal Nodular Hyperplasia(FNH), is the second most common benign tumor of the liver. In our case the young patient was taking several herbal products and dietary supplements including anabolic androgenic steroids (AASs). We have reported a rare case of left hepatectomy for FNH. We suppose that the increasing of the lesion, in two years in which the patient made use of anabolic steroids. Hormonal conditioning of these lesions is known, under use of oral anabolic steroids being proved the increase in volume of FNH. This could be the explanation for increasing of nodule. Abstract: Introduction: Focal Nodular Hyperplasia (FNH) is the second most common benign tumor of the liver. Clinically FNH is asymptomatic and discovered incidentally . The pathogenesis is unclear; FNH is usually asymptomatic. When the tumor is large, it may be painful. Surgery is recommended only in the case of complications such as compression of adjacent organs, lesion progression with tumor size >5 cm and presence of symptoms. Presentation of case: A 30 years old man, was evaluated during a routine visit, for diffuse abdominal pain and weight loss; Abdominal ultrasound showed no evidence of biliary obstruction but the US shows a hypoechoic, well defined focal lesion in the left liver. For a more accurate diagnosis a Magnetic Resonance detected a focal area about 14 × 9 cm in diameter, hypointense. Liver biopsy was not done.We could not diagnose it definitively as FNH from the results of imaging studies; so for the size of symptomatic lesion, the undefined diagnosis of FNH, and due to the great increase in the size of the mass located in the left lobe, during such a short period, the surgery was been recommended. Discussion: FNH is the second most common hepatic lesion, but clinically relevant cases of FNH are rare with a reported prevalence in US studies of 0, 03%. In our case the young patient was taking dietary supplements including anabolic androgenic steroids (AASs), carnitine andl -arginine. Conclusion: The particularity of our case is the increasing of the lesion in two years in which the patient made use of anabolic steroids. under use of . This could be the explanation for increasing of nodule.